Incidence of insect and mite pests in French bean in Assam, India - Sharmah, D; Rahman, S (Indian Journal of Plant Protection, 2020)
The present investigation was carried out in the Integrated Crop Research (ICR) farm, Assam Agricultural University (AAU), Jorhat as well as in the Acarology laboratory, Department of Entomology, AAU, Jorhat during 2013-14 and 2014-15 to record pest complex on French bean and their incidence. Eight insect pests viz., cutworm, Agrotis ipsilon; aphid, Aphis craccivora; thrips, Scirtothrips dorsalis; pod borer, Helicoverpa armigera; whitefly, Bemisia tabaci; leaf beetle, Monolepta signata; leaf miner, Liriomyza sativae; red ant, Dorylus orientalis and two spotted spider mite, Tetranychus urticae were recorded. The incidence of aphid and cut worm was found to be maximum during the 51st Standard meteorological week (SMW) with 1.33 numbers per twig per plant and 1.0 number per plant, respectively. Highest populations of the mite and thrips were recorded during 52nd SMW i.e.1.23 and 0.97 number per leaf, respectively. The incidence of pod borer and whitefly was found to be maximum during the 51st SMW with 1.12 per plant and 52nd SMW with 1.23 numbers per leaf, respectively. The incidence of leaf beetle, leaf miner and red ant was found to be minor.